Comparison of Micro-EDM Characteristics of Inconel 706 between EDM Oil and an Al Powder-Mixed Dielectric - Chenxue Wang; Zhang Qiang (Advances in Materials Science and Engineering)
Inconel 706 is a newly developed aeronautical material that has corrosion resistance along with high mechanical strength. Conventional machining of Inconel 706 results in a poor surface finish and a low-dimensional accuracy. Hence, micro-EDM (electrical discharge machining) is utilized to machine Inconel 706. This work proposes a comparison of micro-EDM characteristics of Inconel 706 between EDM oil and an Al powder mixture. The effects of input parameters on the surface roughness, material removal rate, tool removal rate, and microstructures of the machined surfaces between EDM oil and EDM oil mixed with Al were investigated. It was clarified that micro-EDM with a certain amount of Al powder added to the EDM oil can attain a high MRR and better surface integrity. However, the TWR discharge gap was larger than that in the EDM oil. Furthermore, it was observed that more attachment of the workpiece was adhered to the top surface of the electrode in the EDM oil due to its unstable machining. It was explained that the MRR increases with an increase in the Al concentration and then tends to decline.